What we think we know about newton's principia - Raquel Anna Sapunaru; Gabriela Fernandes (Universidade Federal de Rondônia, 2018)
In this article we examine some of the most controversial points in Newton's Principia regarding the contemporary interpretation: the assumed circularity of Definition I, the difference between vis insita and vis inertia, Law I and Law II. The main goal of this work is to offer a wider view of Newton's writings and provide a historic philosophical approach to the physics teachers which will certainly be useful in physics teaching. We also discuss the modern terminology compared to the one used by Newton himself. Our main concern is to aid the deconstruction of preconceived ideas regarding the Principia which are fairly common among physics teachers.